Non-covalent polymer-protein complexes for pulmonary protein delivery - Nieto Orellana, Alejandro (2017)
Pulmonary delivery of protein and peptide therapeutics has recently received increasing attention to treat both local and systemic diseases. However, to further increase its current clinical impact, numerous challenges including protein degradation, pulmonary clearance and immunogenicity, still need to be addressed. To this aim, in the present work we developed novel non-covalent polymer-protein nanocomplexes to allow reversible conjugation of proteins, and investigate their potential to protect and release them at the target site following pulmonary administration. Accordingly, a family of structurally related block copolymers mPEG2k-poly(glutamic acid) with linear A-B (mPEG2k-lin-polyGA) and miktoarm A-B3 (mPEG2k-mik-(polyGA)3) structure was first synthesised to assess the effect of macromolecular topology of the copolymers on electrostatic polymer-protein complexation, using lysozyme as the model protein substrate. (mPEG2k-lin-GA) and (mPEG2k-mik-(GA)3)-lysozyme nanocomplexes were then formulated into dry powders suitable for pulmonary delivery by spray-drying, using different aerosol excipients. The aerodynamic properties of these dry powders, their ability to efficiently release the nanocomplexes in aqueous environment and their capacity to protect lysozyme from proteolytic enzymes were evaluated. Finally, to improve uptake of nanocomplexes by lung epithelial cells cyanocobalamin (vitamin B12) ligands were introduced within the mPEG2k-polyGA copolymers, and the resulting targeted macromolecules were complexed with lysozyme. These targeted nanocomplexes were then formulated into dry powders and their ability to enhance lysozyme uptake by Calu-3 lung epithelial cells was assessed in vitro, along with their effect on activation of the complement system. Finally, (vitB12- PEG3k-polyGA)-lysozyme dry powder formulations were tested in vivo through administration to healthy BALB/c mice, and pulmonary protein deposition/retention and local pulmonary tolerance were evaluated. Taken together, this study indicates that if complexing polymers are appropriately designed, efficient non-covalent complexation of proteins and peptides can be achieved. Importantly, inclusion within polymer complexes can protect proteins from proteolytic degradation, and when suitable targeted ligands are introduced, increase protein cellular uptake in the lung epithelium, and enhance protein retention in the lungs with minimal toxicity.